The Influence of Digital Marketing, Customers Experience, and Fashion Involvement on Consumer Buying Interest in Bata Products in Medan Mall - Natasya, Apriliana; Pohan, Yulia Arnida (CV. Civiliza Publishing, 2025)
This study aims to determine and analyze the influence partially and simultaneously. Digital Marketing, Customer Experience, Fashion Involvement , and Consumer Purchase Interest in Bata Products at Medan Mall . The type of research used in this study is causal associative research with quantitative methods. The population in this study were consumers who had visited and were interested in purchasing. The sampling technique in this study used a nonprobability sampling method with an accidental sampling technique. To determine the sample size, the researcher used the Lameshow formula. The number of research samples taken in this study was rounded from 98 to 124 respondents to avoid biased data. The results of the partial test showed that Digital Marketing has a positive and significant effect on consumer purchase intention, Customer Experience does not have a significant effect on consumer purchase intention , and Fashion Involvement has a positive and significant effect on consumer purchase intention. Meanwhile, the results of the simultaneous test show that Digital Marketing, Customer Experience, and Fashion Involvement have a positive and significant effect on consumer purchase intention. together have a positive and significant influence on Consumer Purchasing Decisions on Bata Products in Medan Mall . The adjusted R square value of 0.418 can be called the coefficient of determination, this means that 0.418 (41.8%) of Purchase Interest can be obtained and explained by Digital Marketing, Customer Experience and Fashion Information while the remaining 58.2% is explained by variables outside the model that were not studied .